Efficacy and safety of aflibercept plus chemotherapy in metastatic colorectal cancer: A systematic review and PRISMA‐Compliant single‐arm Meta‐Analysis of noncomparative clinical studies and randomized controlled trials. (1st March 2022) - Ge, Pu; Reyila, Abudurosuli; Li, Xin‐yi; Liu, Si‐yu; Jiang, Yi‐xuan; Yang, Ya‐jie; Li, Xia‐lei; Bian, Ying
Abstract: What is known and Objective: Aflibercept, a recombinant protein designed to suppress the vascular endothelial growth factor (VEGF) signalling pathway, has been used in patients with metastatic colorectal cancer (mCRC). We conducted the first meta‐analysis to systematically review the efficacy and safety of aflibercept in mCRC. Methods: PubMed Central/Medline, Embase and cochrane library were systematically searched for randomized controlled trials and single‐arm clinical trials on aflibercept plus chemotherapy for the treatment of mCRC through 9 September 2021. Results: Ten studies comprising 2049 patients met the inclusion criteria. The pooled estimate rates were 16.0% for 12mPFS, 64.4% for 12mOS, 32.5% for ORR, 83.5% for DCR, while the rates of III/IV AEs rate were 80.2% respectively. The pooled estimate rates were 16.8% for III/IV diarrhoea, 22.3% for III/IV hypertension, 29.5% for III/IV neutropenia, 7.3% for III/IV proteinuria and 8.6% for III/IV oral mucositis. Conclusions: Analysis of data from randomized controlled trials(RCT) and single‐arm clinical trials confirmed the good efficacy of aflibercept plus chemotherapy in mCRC, while the safety of the treatment is concerning. Abstract : We performed the first meta‐analysis of aflibercept plus chemotherapy in metastatic colorectal cancer, which demonstrates that aflibercept plus chemotherapy has good efficacy in the second‐line treatment of metastatic colorectal cancer, but the safety of this kind of therapy is worrisome.